Implementation of the Integrated Service Center Program for Child Empowerment and Protection against Domestic Violence in Bekasi Regency - Anton Junata; Junifer Dame Panjaitan (Jurnal Restorasi : Hukum dan Politik, 2023)
The increasing number of violence against women in the household prompted the government to create an Integrated Service Center for Child Empowerment and Protection program to prevent and protect victims of violence. This research aims to find out how the P2TP2A program works. By using qualitative research methods, researchers will explain the results of observations that have been made. Even though it has not run optimally, P2TP2A has provided a sense of security and protection to victims of violence.